AN OVERVIEW OF TYPES OF VERBS: CLASSIFICATION AND LINGUISTIC ANALYSIS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation: Verbs are fundamental components of language, playing a crucial role in expressing actions, states, and relationships. This scientific article provides an extensive overview of the various types of verbs found in natural languages. By examining their classification and linguistic properties, we aim to deepen our understanding of verb structures and their functions within sentences. This analysis encompasses action verbs, stative verbs, auxiliary verbs, modal verbs, phrasal verbs, and irregular verbs, shedding light on their distinct characteristics and linguistic implications.